Radiographic Stent for Simplified Placement of Implants in the Mandible - Zargar, Nazia Majeed (Journal of Orofacial Research, 2013)
This article aims to present a modified yet simple technique for the placement of implants between the mandibular foramina with the help of a radiographic stent. A radiographic stent was made on the patient’s mandibular cast on which two metal balls were fixed at the premolar area and this was then used to determine the exact position of the mental foramina with the help of a panoramic X-ray. After visualization of the distance between the metal balls and mental foramina, the radiographic stent was used as a surgical guide to place implants in themandible during surgery.